The problem of Local Government Indebtedness in Poland: A Critical Approach - Krzysztof SUROWKA (Communications of International Proceedings, 2021)
An important feature of local government, differentiating it from other public authorities, is the independence of its bodies from the government administration system. Independence, including the financial independence of local government is determined in most countries by acts of law of the highest rank, including fundamental laws. However, the scope of financial independence is a significant problem of the local government. The integrity of local government finances with the system of public finances and, at the same time, the political and legal independence of local government are the reason for numerous discussions related to its functioning. The clash of two opposing theories of local government, i.e. the naturalistic theory referring to the principle of subsidiarity and grass-roots self-organisation of the state and the state theory treating local government as a system of state management, has been the source of numerous doubts as to what the actual scope of the local government's financial independence should be. The presented article focuses on some problems related to the issues of local government units indebtedness of in Poland.
Keywords: Current Revenues; Current Expenditures; Financial Independence; Indebtedness; Local Government Units (Lgus); Operating Surplus; Poland.